SINTESIS BIOSURFAKTAN EKSTRAK DAUN PURING (Codiaeum variegatum) DAN KULIT JERUK PURUT (Citrus hystrix) SEBAGAI DETERGEN BIODEGRADABLE - Sitti Chadijah; Sarah Nurmayanti; Rahmiani Gani; Ummi Zahra; Iin Novianty (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Croton leaf (Codiaeum variegatum) and kaffir lime peel (Citrus hystrix) are plants that contain secondary metabolite compounds such as saponins and tannins. This research aims to utilize natural ingredients to biodegradable detergent synthesis and determine the quality of the biosurfactant product produced. The detergent composition was made using 5 variations of extract concentration, namely 15%, 30%, 45%, 50% and 55%. Analysis of the quality of detergent products includes organoleptic tests, pH tests, density tests, viscosity tests, foam height and foam stability tests as well as saponin and tannin levels contained therein before and after making the detergent. The detergent quality results obtained met SNI standards, namely pH 5-10, density 1.3 g/cm3, viscosity ranging from 3-20 cP, foam height 3-13 cm and foam stability 66.6% - 92.5%. Total saponin levels increased after making detergent and tannin levels decreased after making detergent. These results proved that croton leaf and kaffir lime peel can be used as raw materials for biodegradable detergent.